Efficacy of botulinum toxin type A in treatment of different forms of focal dystonias in the Serbian population: experience of the Botulinum Toxin Outpatients Department - Tomić, Aleksandra; Vujović, Balša; Dragašević Mišković, Nataša; Petrović, Igor; Pekmezović, Tatjana; Kostić, Vladimir S (Vojnosanitetski pregled, 2016)
Background/Aim. Botulinum toxin (BTX) irreversibly inhibits presynaptic acetylcholine release with subsequent relaxation of abnormally contracting muscles. It is an effective and well tolerated treatment with long-term benefit in a variety of movement disorders and other neurological and non-neurological disturbances. The aim of our study was to present our experience with BTX type A in treatment of different forms of focal dystonias. Мethods. А hundred of patients with different focal dystonias (spastic torticollis, blepharospasm and graphospasm) from the Botulinum Toxin Outpatients Department, Clinic for Neurology, Clinical Center of Serbia, were included in the study. All the patients were examined and rated at baseline visit prior to BTX application and on the following visit, after 3–4 months, using self-assessment improvement questionnaire and standardized rating scales. Results. The improvement of ≥ 50%  was presented in 68.2% of all (199) the analyzed applications. Independent predictors of good response to the therapy (improvement ≥ 50%) were male sex (p = 0.011), the presence of sensory trick (p = 0.013) and the total number of BTX applications (p = 0.002). The patients with spastic torticollis and blepharospasm showed a statistically significantly better BTX effect (improvement 57.3 ± 27.5% and 54.1 ± 28.3%), respectively than the graphospasm group (26.7 ± 25.6%). Most of the patients did not have therapy complications (81.4% and 72% in two applications). Side effects in the remaining patients (muscle weakness, dysphagia, ptosis, double vision, neck weakness and lacrimal dysfunction) lasted for 28.3 ± 18.6 days after the first treatment and 32.5 ± 36.2 days after the second one. Conclusion. BTX is safe and highly effective in long-term treatment of patients with different forms of focal dystonia, with only mild and well- tolerated side-effects. Key words:dystonia; botulinum toxins; serbia; questionnaires; quality of life